Attribution of Lineage of Adopted Children in Indonesian Law: A Comparative Analysis of the Child Protection Law and the Compilation of Islamic Law - Dulsukmi Kasim Dulsukmi; Rivai Arifin Rivai; Rizal Darwis Rizal; Abdur Rahman Adi Saputera; Sofyan AP Kau Sofyan (At-Tafkir, 2026)
The legal status of the lineage (nasab) of adopted children remains a contested issue in Indonesia due to the coexistence of national law and Islamic family law. While Indonesia's Child Protection Law (UUPA) prioritizes the protection and welfare of children, the Compilation of Islamic Law (KHI) upholds the principle of preserving biological lineage, creating potential differences in legal interpretation and application regarding the relationship between adopted children and their adoptive fathers. This study aims to compare the legal provisions of the Child Protection Law and the Compilation of Islamic Law concerning the attribution of lineage to adopted children and to examine the extent to which these two legal frameworks can be harmonized. Employing a normative-comparative legal approach, this research analyzes statutory regulations, legal doctrines, and relevant scholarly literature through qualitative legal analysis. The findings demonstrate that both legal frameworks consistently reject the transfer of biological lineage from biological fathers to adoptive fathers. However, they differ in their underlying legal philosophy and practical implications. The Child Protection Law adopts a child-centered approach that emphasizes legal protection and the fulfillment of children's rights without altering biological identity, whereas the Compilation of Islamic Law is grounded in the Islamic legal principle of preserving nasab as an essential objective of family law. These findings suggest that the two legal systems are complementary rather than contradictory, as they pursue different legal objectives while reaching a similar conclusion regarding the non-transferability of lineage. The study contributes to the development of a more coherent framework for harmonizing national child protection policies with Islamic family law and provides a normative reference for legislators, judges, and legal practitioners in resolving adoption-related disputes in Indonesia.